Shaping business sector transformations (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
The climate crisis requires a transformation towards a climate-neutral economy. This implies considerable pressure for business sectors with a high carbon footprint. The key challenge here is to shape the structural change in a way that is ecologically, economically and socially successful.